Research and statistical methods in communication sciences and disorders - Maxwell, David L.
This book provides comprehensive coverage of research methods as well as a foundation in statistical analysis vital for individuals in the communication sciences and disorders field. While most speech-language pathologists and audiologists pursue clinical practice rather than research careers, it is important to understand the scientific base that their clinical work is built upon